The comparative jurisprudence of wildfire mitigation: moral community, political culture, and policy learning$dLloyd Burton - Burton, Lloyd (Oñati Socio-Legal Series, 2013)
The cultural and societal diversity in the jurisprudence of living dangerously reflects equally diverse views on the deeper question of law’s moral purpose. What duty of care does (or does not) a community owe to those at the greatest risk of harm to their homes and persons? And is there also a right to be left alone—to assume all the risks and all the responsibilities for one’s own well-being, neither helped nor hindered by the community of which one is a part? This article reports comparative research being done on two states in the U.S. that have used the law to answer these morally freighted questions in very different ways, with specific regard to land use regulation in forested areas where wildfires have taken many lives and destroyed billions of dollars in residential property.It also suggests how this same analytic framework might be applied to transnational research in other legal cultures also endangered by catastrophic wildfires, such as Australia and Spain.